2013
DOI: 10.1111/1556-4029.12094
|View full text |Cite
|
Sign up to set email alerts
|

Fracture Characteristics of Entrapped Head Impacts Versus Controlled Head Drops in Infant Porcine Specimens,,

Abstract: In many forensic cases, the job of forensic pathologists and anthropologists is to determine whether pediatric death is due to an abusive act or an accidental fall. The goal of this study was to compare the cranial fracture patterns generated on the parietal bone of a developing, infant porcine (pig, Sus scrofa) model by a controlled energy head drop onto a plate versus previous data generated by blunt force impact at the same energy onto the head constrained to a plate. The results showed that blunt force imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(38 citation statements)
references
References 29 publications
(74 reference statements)
2
35
1
Order By: Relevance
“…Porcine bone is believed to be a suitable human bone substitute in fracture research and has been used as a model in many forensic studies [3,[15][16][17]34,35]. Isolated porcine heads were used in the current study.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Porcine bone is believed to be a suitable human bone substitute in fracture research and has been used as a model in many forensic studies [3,[15][16][17]34,35]. Isolated porcine heads were used in the current study.…”
Section: Methodsmentioning
confidence: 99%
“…It has previously been shown that rigid restraint of specimens during impact testing alters the stress distribution which results in a greater amount of fractures occurring as well as more fractures occurring remote to the site of impact [17,25,36]. The suspension system utilised in this study allowed for the free movement of the head after impact, limiting the chance of false fractures occurring due to restraint and thus ensuring that any trauma inflicted upon the specimen was due specifically to the impact.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cranial fracture characteristics from the carpet impacts were also compared to the previously published low‐energy rigid interface head drop data of Powell et al. . As previously described, this study utilized impact energy levels approximately twice those of the Powell et al.…”
Section: Resultsmentioning
confidence: 99%
“…These energy levels were set to be approximately twice those of the Powell et al. study in order to generate a greater degree of cranial fracturing across the surfaces of varying compliance.…”
Section: Methodsmentioning
confidence: 99%